Quantitative evaluation of photoaging mechanisms using analysis of photoacoustic images - Takeshima, Haruna; Namita, Takeshi; Kondo, Kengo; Yamakawa, Makoto; Shiina, Tsuyoshi (Transactions of Japanese Society for Medical and Biological Engineering, 2021)
In recent years, skin aging caused by ultraviolet light exposure has garnered attention in the fields of beauty and health care because photoaging accelerates skin aging. Elastin is closely related to photoaging. Histopathological diagnosis is the conventional method for evaluating the photoaging skin. However, this diagnosis is invasive and has no metabolic function, and its mechanism has not been fully clarified. In this study, photoacoustic imaging was employed for evaluating photoaging mechanisms. This study used acoustic resolution photoacoustic microscopy. An ultrasonically focused transducer attached to the imaging head detected photoacoustic waves. Photoacoustic signal distributions of various photoaging sections were measured. To examine the distinguishability between elastin and collagen, the signal intensity ratio of wavelength 420/450 nm was calculated. The signal intensity ratio of the collagen part is higher than that of elastin part. These results verified the possibility of discriminating elastin from collagen using multi-wavelength analysis of photoacoustic images.